2021
DOI: 10.1371/journal.ppat.1008909
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic translation initiation factor 5A and its posttranslational modifications play an important role in proliferation and potentially in differentiation of the human enteric protozoan parasite Entamoeba histolytica

Abstract: The eukaryotic translation initiation factor 5A (eIF5A) is a highly conserved protein and is essential in all eukaryotes. However, the specific roles of eIF5A in translation and in other biological processes remain elusive. In the present study, we described the role of eIF5A, its posttranslational modifications (PTM), and the biosynthetic pathway needed for the PTM in Entamoeba histolytica, the protozoan parasite responsible for amoebic dysentery and liver abscess in humans. E. histolytica encodes two isotype… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Deoxyhypusine synthase (DHPS)-driven eIF5A hypusination was recently shown to be a feature of proinflammatory macrophages, and DHPS deletion in macrophages resulted in improved insulin sensitivity and glucose homeostasis. Furthermore, hypusination is being increasingly implicated in metabolic diseases and microbial infections [213,214], hypusine polyamine precursors have been reported in intestinal epithelial renewal and M2 macrophage polarization [215], and dietary spermidine was recently shown to boost eIF5A hypusination and protect mitochondrial dysfunction during brain aging [216]. The polyamine pathway intermediate spermidine was recently reported to induce anti-inflammatory pathways following release from apoptotic cells [217]; it has protective effects in metabolic diseases and has emerged as a well-tolerable caloric restriction mimetic and provider of nitric oxide and arginine bioavailability [218].…”
Section: Pro-ferroptotic Labile Iron Pool (Lip) and Rna-binding Prote...mentioning
confidence: 99%
“…Deoxyhypusine synthase (DHPS)-driven eIF5A hypusination was recently shown to be a feature of proinflammatory macrophages, and DHPS deletion in macrophages resulted in improved insulin sensitivity and glucose homeostasis. Furthermore, hypusination is being increasingly implicated in metabolic diseases and microbial infections [213,214], hypusine polyamine precursors have been reported in intestinal epithelial renewal and M2 macrophage polarization [215], and dietary spermidine was recently shown to boost eIF5A hypusination and protect mitochondrial dysfunction during brain aging [216]. The polyamine pathway intermediate spermidine was recently reported to induce anti-inflammatory pathways following release from apoptotic cells [217]; it has protective effects in metabolic diseases and has emerged as a well-tolerable caloric restriction mimetic and provider of nitric oxide and arginine bioavailability [218].…”
Section: Pro-ferroptotic Labile Iron Pool (Lip) and Rna-binding Prote...mentioning
confidence: 99%
“…Since eIF5A is highly conserved and is essential to all eukaryotes it may represent a new option for a pharmacological targeting of various diseases due to eukaryotic pathogens. A recent study by Jeelani and Nozaki [ 107 ] reported that eIF5A and its post-translational modification is essential for both proliferation and differentiation of Entamoeba histolytica , the protozoan responsible for amoebic dysentery and liver abscess in humans. They showed that Entamoeba eIF5A is involved in excystation, conversion from the cyst to the trophozoite, but not in encystation.…”
Section: Anti-parasitic Therapymentioning
confidence: 99%